The Impact of Understanding Financial Literacy on Student Financial Behavior - Zidnaa Luthfa Hudaaka; Verbena Ayuningsih Purbasari (Prodi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Ponorogo, 2024)
Introduction: Financial literacy is an important aspect in determining the direction and decisions on individual financial behavior. In this case, students who should have a good level of understanding of financial literacy are trapped in a series of financial problems. Research Method: To be able to obtain an appropriate analysis and be able to interpret the data properly, a qualitative method with a phenomenological approach and interpretative phenomenological analysis was used. Based on the results of the analysis using interpretative phenomenological analysis, it is found that financial literacy has a very strong and inherent relationship to student financial behavior. Result: The result can be formulated that the level of financial literacy of FEBI IAIN Ponorogo students tends to be at the sufficient-less literate level. The measurement is done using four aspects of financial literacy assessment proposed by Chen and Volpe. Furthermore, there are several factors that influence the understanding of financial literacy, such as sociodemographic factors, financial knowledge, financial behavior, financial attitudes and financial training owned by students. Finally, the impact of students' low understanding of financial literacy results in unplanned and disorganized spending, difficulty saving and managing emergency funds, inappropriate decision making, getting stuck in the debt cycle, and the psychological impact of financial problems experienced. Conclusion: The poor understanding of financial literacy has a negative impact on students' financial behavior. In particular, it even has a serious impact on their financial behavior, leading to debt bondage and a series of other financial problems.